2018
DOI: 10.18521/ktd.430081
|View full text |Cite
|
Sign up to set email alerts
|

Östrojen-Progesteron Reseptörü Pozitif ve Aksiller Lenf Nodu Negatif Meme Kanseri Tanılı Hastalarda Ki-67 Proliferasyon İndeksi

Abstract: Ki-67 hücre siklusunda G0 fazı dışında eksprese edilen nükleer bir proteindir. Prolifere olan hücreleri gösteren belirteç olarak kullanılmaktadır. Meme kanseri tanılı hastalarda Ki-67 proliferasyon indeksinin kötü klinik sonuçlarla ilişkili olduğu gösterilmiştir. Bu çalışmada östrojen reseptörü ve progesteron reseptörü pozitif, HER-2 negatif, aksiller lenf nodu tutulumu bulunmayan meme kanseri tanılı hastalarda Ki-67 proliferasyon indeksinin prognostik öneminin değerlendirilmesi amaçlanmıştır. Gereç ve Yöntem:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Small, low-grade tumors with low rates of axillary involvement are more likely to belong to the ER + PR ± HER2-group. 29 Bolat Küçükzeybek et al reported a positive correlation of KI-67 proliferation index with histological grade and tumor size, as well as a poor effect at 7-year OS 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Small, low-grade tumors with low rates of axillary involvement are more likely to belong to the ER + PR ± HER2-group. 29 Bolat Küçükzeybek et al reported a positive correlation of KI-67 proliferation index with histological grade and tumor size, as well as a poor effect at 7-year OS 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells are classified as hormone receptorpositive or negative, depending on their receptor expression profile. Knowing the expression status of the hormone receptor is an essential factor in selecting the treatment strategy to be applied (38). In the follow-up of this section, basic information about the ER protein, which is known to be closely associated with breast cancer, and signaling pathways controlled by the ER will be shared.…”
Section: Breast Cancer Associated Receptorsmentioning
confidence: 99%